Detectability of Hygroscopic Clips Used in Breast Cancer Surgery. (31st December 2016) - Carmon, Moshe; Olsha, Oded; Gekhtman, David; Nikitin, Irena; Cohen, Yamin; Messing, Michael; Lioubashevsky, Natali; Abu Dalo, Ribhi; Hadar, Tal; Golomb, Eliahu
Abstract : Sonographically detectable clips were introduced over the last decade. We retrospectively studied the rate and duration of sonographically detectable clip detectability in patients with breast cancer who had sonographically detectable clips inserted over a 2‐year period. Nine of 26 patients had neoadjuvant chemotherapy, with all clips remaining detectable 140 to 187 days after insertion. Six of the 9 had intraoperative sonographic localization, with 1 reoperation (17%). Eleven additional patients with nonpalpable tumors and sonographically detectable clips had intraoperative sonographic localization with 1 reoperation (9%). In 1 patient, a sonographically detectable clip enabled intraoperative identification of a suspicious lymph node. There were no complications or clip migration. Sonographically detectable clips are helpful in breast cancer surgery with and without neoadjuvant chemotherapy, remaining detectable for many months and often averting preoperative localization and scheduling difficulties.